Karakteristik Komposit Biotermoplastik Dalam Variasi Formulasi Pati Termoplastis, Glukomanan Termoplastis dan Poli Asam Lakta - Harianja, Berkat; Harsojuwono, Bambang Admadi; Triani, I Gusti Ayu Lani; Hartiati, Amna; Suhartini, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Determination of biothermoplastic composite formulation is essential to produce the best biothermoplastic composite characteristics and meet the standards. This study seeks to identify the characteristics of the best biothermoplastic composites in variations of thermoplastic starch formulations, thermoplastic glucomannan and polylactic acid. This study used a Completely Randomized Design (CRD) with 5 treatments of TPS/TPG formulas with PLA, namely 90:10, 80:20, 70:30, 60:40, 50:50. There were 4 repetitions of each treatment, for a total of 20 experimental units. The variables observed were tensile strength, elasticity, elongation at break, melting point, biodegradation, swelling and density. The diversity analysis showed that the formulation of thermoplastic starch-thermoplastic glucomannan and polylactic acid had a very significant effect on the tensile strength, elasticity, elongation at break, melting point, biodegradation, swelling and density of biothermoplastic composites. Biothermoplastic composites with the formulation of TPS/TPG: PLA = 50:50 produced the best characteristics with a tensile strength of 26.71 MPa, elasticity of 932.04 MPa, elongation at break of 2.89%, biodegradation of 15.25 days, melting point of 152.65oC, density of 1.26 g/cm3 and swelling of 1.32%.